STRUKTUR MUSIK KONCONG DI DESA BABANE KECAMATAN SAMALANTAN KABUPATEN BENGKAYANG - Asari, Wiwi; Istiandini, Winda; Silaban, Chiristianly Yery (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research was motivated there is not provision of the punch pattern and koncong music melody, making the researcher interested in conducting the research on the structure of Koncong music in Babane Village, Samalantan District, Bengkayang Regency. The purpose of this research was to describe the structure of Koncong music in Babane Village, Samalantan District, Bengkayang Regency. The research method was descriptive method. The research design was qualitative. The data of this research were the results of interviews, observations, the results of documentation and field note regarding the Koncong music. The data collecting techniques of this research were observation, direct communication and documentary study. The data collecting tools of this research were researchers as the main instruments, interview guidelines, observation guidelines and documentation tools. The validity of the data testing techniques were extension of observation, and the source triangulation.The data analysis technique of this research was data reduction, data presentation, and conclusion.The results of this research indicated that Koncong music uses the B Major scale was played with 4/4 of the time and the tempo of Moderato.This research result can be option for a teaching material in culture arts learning in Junior High School.Keywords: Koncong, Music, Structure